Djerba patrimoine mondial : ateliers d'été du 16 au 25 juillet 2018 du 15 au 31 juillet 2019 - Djerbi, Ali; Chaabani, Mouldi (ENAU/ESAD, 2019)
Keywords: Architecture -- Djerba; Attushi, mosquée al- (Wersighen, Djerba); Monuments -- Djerba; Mughzal, mosquée (Beni Maaguel, djerba); Sidi Abd Allah, mosquée (Mezrane, Djerba)

قراءة نقدية في تجربة ترميم وصيانة التراث المعماري بجزيرة جربة من الاستقلال إلى اليوم - الطبجي بن رجب, نجوى (كلية العلوم الإنسانية والإجتماعية, 2016)
Keywords: Ammi Yathi, mosquée (Fahmine, Djerba); Architecture -- Djerba; Bardawi, mosquée al- (Mezrane, Djerba); Ben Biyan, mosquée (Majmaj, Djerba); Bin Ma'zuz, mosquée (Mezraya, Djerba); Ghuraba, mosquée al- (Houmt Souk, Djerba); Hâra, mosquée al- (Sedouikech, Djerba); Jaddi Isa, mosquée (Robbana, Djerba); Monuments -- Djerba; Mughzal, mosquée (Beni Maaguel, djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Jmur, mosquée (El Groo, Djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Walḥī, mosquée (Oued Zbib, Djerba)

تنظيم المجال والتوطين والتعمير بجزيرة جربة في العهد الوسيط أطروحة الدكتوراه في علوم التراث - بربو, المنصف (كلية العلوم الانسانية والاجتماعية, 2017)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Muhammad Kammus, mosquée (Hachene, Djerba); Abu Smayil, mosquée (Mezrane, Djerba); Abu Zakariyya Fasil, mosquée (Bani Bandou, Djerba); Ammi Yathi, mosquée (Fahmine, Djerba); Ben Biyan, mosquée (Majmaj, Djerba); Bin Ya'lâ, mosquée (Erriadh, Djerba); Bin Yakhlaf, mosquée (Guechaine, Djerba); Bûkhtîr, mosquée (Taghdimes, Djerba); Bûlaymân, Mosquée (Cedghiane, Djerba); Ghuraba, mosquée al- (Houmt Souk, Djerba); Hâra, mosquée al- (Sedouikech, Djerba); Jaddi Isa, mosquée (Robbana, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Monuments -- Djerba; Mthaniya, mosquée al- (Ajim, Djerba); Mughzal, mosquée (Beni Maaguel, djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Garus, mosquée (Haddada, Djerba); Sidi Khalifa, mosquée (Houmt Arbah, Djerba); Sidi Sabbaḥ, mosquée (Tezdaine, Djerba); Sidi Salama, mosquée (Erriadh, Djerba); Sidi Salih, mosquée (Bani Bandou, Djerba); Sidi Waḥlan, mosquée (Haddada, Djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîfarrûjîn, mosquée (Oualagh, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba); Walḥī, mosquée (Oued Zbib, Djerba)

Les femmes berbères dans les sources ibadites du Maghreb médiéval - Prevost, Virginie (Written sources about Africa and their study, 2018)
Keywords: Monuments -- Djerba; Mughzal, mosquée (Beni Maaguel, djerba)

Guarding a Well-Ordered Space on a Mediterranean Island - Holod, Renata; Kahlaoui, Tarek (The Archaeology of Medieval Islamic Frontiers, 2019)
For Ifriqiya, the Maghrib, and the eastern coast of al-Andalus, a ribāṭ can be defined as a coastal point of defense meant to host ghazīs, warriors for the faith or volunteers on the basis of religious commitment. From the eighth century onward, ribāṭs stretched along the seashore of Islamic Maghrib from Tripoli (Ṭarāblus) up to the east coast of al-Andalus. These were typically connected to another urban structure with an immediately supporting rural environment, or they could be isolated structures supplied from the sea. In one sense, they functioned in much the same way as stations along the ‘Abbasid-Byzantine land
Keywords: Archéologie -- Djerba; Hâra, mosquée al- (Sedouikech, Djerba); Monuments -- Djerba; Mughzal, mosquée (Beni Maaguel, djerba)